Sex differences in microglial CX3CR1 signalling determine obesity susceptibility in mice - Mauricio D. Dorfman (Nature Portfolio, 2017)
Unlike males, female mice are resistant to hypothalamic inflammation and weight gain when fed a high-fat diet. Here, the authors reveal sex-specific regulation of hypothalamic microglial activation through CX3CR1 signalling, providing a potential mechanism for differential susceptibility to diet-induced obesity.